A Comprehensive Method of Ion Exchange Resins Regeneration and Its Optimization for Water Treatment - Al-Asheh, Sameer (2020)
Ion exchange membranes, specifically resin technology, lie at the heart of electrolytically conductive systems used in the treatment of wastewater. This chapter deals with ion exchange deionization and the effect of resin amount as well as the concentration of acid and base on the product conductivity. The strong acidic cation polymeric exchanger resin is commercially called MERCK 104765 cation exchanger IV with capacity greater than 3.2 mmol/ml, while the strong basic anion polymeric exchanger resin is commercially called MERCK 104767 anion exchanger III with capacities greater than 1.0 mmol/ml. Water conductivity, as an indicator of regeneration efficiency, was monitored over time at the different conditions and scenario. In general, it was observed that the conductivity decreases with time until one point is reached and then starts to increase as a result of resin saturation. It was also noticed that the lowest conductivity is achieved when using 1-vol% NaOH and 5-vol% HCl in the cathodic and anodic resin tubes, respectively, and that water conductivity increases with the increase in the amount of water being used. The amount of resin significantly impacts the deionization efficiency; more ions are removed as the amount of resin increases.